THE ROLE OF INTERACTIVE TEACHING METHODS IN THE DEVELOPMENT OF MENTAL ACTIVITY AND THE ASSIMILATION OF STUDENTS' KNOWLEDGE AT A UNIVERSITY - Akramova, Lola Yunusovna; Mirzaeva, Shakhlo Ruzmat-Kizi; Makhametova, Dilnavoz Botirovna; Lutfullaeva, Hulkar Asatullaevna (International Journal of Psychosocial Rehabilitation, 2020)
This article is written with the aim of theoretically substantiating the role of interactive teaching methods in the development of mental activity and the assimilation of students' knowledge at a university. The following tasks were identified and solved: to study the psychological and pedagogical foundations of the development of mental activity of students of 1-2 courses; to identify the relationship between the development of mental activity with teaching methods and the development of students' knowledge; to develop a methodology aimed at the effective assimilation of knowledge using interactive teaching methods of students in universities; to determine the features of the development of knowledge in girls and guys in the process of introducing interactive teaching methods; to carry out experimental work to verify the effectiveness of the proposed methodology in improving the development of knowledge by students in the process of implementing interactive teaching methods.